Spatial Pattern of Wild Orchids in Battambang Province, Cambodia - Net Si; Sovanndary Nuon; Mardy Serey (Yayasan Adra Karima Hubbi, 2024)
KESORKOL, scientifically known as Orchidaceae, is a captivating genus of flowering plants endemic to Cambodia. Despite its significance, scientific research on wild orchids in Cambodia has been limited, leading to concerns about the preservation of these unique species. To address this knowledge gap, a study was conducted over 22 months in Battambang province to identify and document wild orchids. The research focused on four districts, resulting in the discovery of 642 individual orchids belonging to 79 species and 38 genera. The study aimed to determine the genera, species, habitats, and locations of wild orchids in Battambang. This information is crucial for understanding their distribution and developing effective conservation strategies. Given the historical lack of extensive research on Cambodian orchids, it is imperative to conduct comprehensive scientific studies to identify rare and valuable species. Such efforts are essential for preserving the country's rich biodiversity.